Grammatical Errors in Writing English Text Made by Students at SMAN 1 Poso Pesisir Selatan - Sherliane Trisye Poai (Sintuwu Maroso Journal of English Teaching, 2020)
The objective of the research was to describe the grammatical errors were found in writing English Text Made by Tenth-grade students at SMA Negeri 1 Poso Pesisir Selatan. The method of the research used a descriptive method. The findings of the research were grammatical errors on writing of SMA Negeri 1 Poso Pesisir Selatan, The kinds of grammatical errors are error in using verb form, word order, subject/verb agreement, pronoun, spelling, capitalization, preposition, article, and adverb. The highest error is error of sentence fragment tenses (23,83%)